Islamic and Socially Responsible Indices: A Case Study of Dow Jones Islamic Market Sustainability Index - EL KHAMLICHI, Abdelbari (International Journal of Islamic Economics and Governance, 2024)
Ethical indices provide the investors with the opportunity to invest according to their choices and beliefs. They could either be socially responsible or morally responsible, Islamic indices belong to the second category. On the one hand, the compliance of socially responsible indices focuses on Corporate Social Responsibility (CSR) practices and Environmental, Social, and Governance (ESG) considerations, by applying some strategies such as: best practices, best in class or shareholders advocacy. On the other hand, Islamic indices apply both qualitative screens (by excluding some companies belonging to the prohibited sectors) and quantitative screens (by excluding companies based on their ratios of debt, receivables and cash). In addition to the divergences between socially responsible indices, and Islamic stock indices, many convergences exist, especially their ethical aspect. Dow Jones Islamic Market Sustainability Index (DJIMSI) » has been launched in January 2006, to be the first index in compliance with both Shariah and social investment guidelines. This category of indices attracted the interest of many researchers, and an important literature review has analysed them theoretically or empirically. In this article, the researcher analyzed Islamic and socially responsible indices taking into consideration their context, to compare the similarities and the differences between their screening criteria. In addition, it provides evidence from DJIMSI over the period 2014-2024. It was also found that DJIMSI was highly correlated to his conventional benchmark, showing the same return rates from September 2014 to December 2019. However, from January 2020 to September 2024, DJIMSI outperforms the conventional index.